2013
DOI: 10.5551/jat.15040
|View full text |Cite
|
Sign up to set email alerts
|

Cut-Off Value of Brachial-Ankle Pulse Wave Velocity to Predict Cardiovascular Disease in Hypertensive Patients: A Cohort Study

Abstract: Aim: Arterial stiffness has been reported to correlate with cardiovascular disease (CVD). Brachialankle pulse wave velocity (baPWV) is easy to measure and has been used as a marker to evaluate arterial stiffness. The objective of the present study was to determine the cut-off value of baPWV for predicting cardiovascular prognosis in a prospective cohort study. Methods: Four hundred forty patients with essential hypertension were analyzed in study 1 with a mean follow-up of 6.3±0.1 years. Four hundred patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 23 publications
1
48
2
Order By: Relevance
“…We excluded 5506 subjects from the analyses (the details of the exclusions and inaccurate baPWV measurement 25 are described in Appendix S1 in the online-only Data Supplement). A final total of 13 381 subjects from 7 cohorts were included in the analysis for all-cause mortality (5 published studies 12,13,15,17,18 and 2 unpublished studies 14,16 ), and 14 673 participants from 8 studies (5 published studies 12,13,15,17,18 and 3 unpublished studies 11,14,16 ) were included in the analysis for CVD risk.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded 5506 subjects from the analyses (the details of the exclusions and inaccurate baPWV measurement 25 are described in Appendix S1 in the online-only Data Supplement). A final total of 13 381 subjects from 7 cohorts were included in the analysis for all-cause mortality (5 published studies 12,13,15,17,18 and 2 unpublished studies 14,16 ), and 14 673 participants from 8 studies (5 published studies 12,13,15,17,18 and 3 unpublished studies 11,14,16 ) were included in the analysis for CVD risk.…”
Section: Study Populationmentioning
confidence: 99%
“…This collaborative study included the data from 14 cohort studies conducted in Japan (9 published and 5 unpublished studies). [11][12][13][14][15][16][17][18][19][20][21][22][23][24] The study was conducted with the approval of the Ethical Guidelines Committee of Tokyo Medical University (No 2655. Figure 1 depicts the process used to select the study population.…”
Section: Study Populationmentioning
confidence: 99%
“…Previous reports have shown that baPWV was correlated well with cfPWV and predicted worse outcomes in hypertensive patients [29,30]. These studies suggest that the baPWV cut-off value was approximately 1750 cm/s, which was associated with increased cardiovascular events and mortality [9,10,31,32]. In this study, an overall prevalence of baPWV of more than 1750 cm/s was 11.9%.…”
Section: Discussionmentioning
confidence: 53%
“…A threshold of >1,750 cm/s for the baPWV was determined for the presence of SOD, which was the cut-off value of baPWV for predicting cardiovascular disease in previous studies [9,10].…”
Section: Definitions Of the Primary Outcomementioning
confidence: 99%
“…For example, the well-known study by Kawai et al [10,11] used baPWV as a measure of arterial stiffness. Its validity and utility have been proven in various clinical settings [12][13][14][15][16][17] and in meta-analyses [18,19], and many studies have investigated its clinical significance [9,20].…”
Section: Introductionmentioning
confidence: 99%